Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Model TGT Berbantuan Media Laci Kartu Soal - Silvia Ibni Harja; Henry Suryo Bintoro; Himmatul Ulya (Limacon: Journal of Mathematics Education, 2019)
This study aims to describe the improvement of problem-solving abilities, student learning activities, and teacher teaching skills in Teams Games Tournament (TGT) model assisted by questions card drawers on perimeter and area materials. This classroom action research was conducted at SD 6 Jekulo with 35 students as research subjects. The study was conducted through 2 cycles, consisting of three meetings. Each cycle there are 4 stages, namely planning, implementation, observation, and reflection. The independent variable in this study is the TGT model aided by the question card drawer, while the dependent variable is the mathematical problem-solving ability, student learning activities, and teacher teaching skills. Data collection techniques used were interviews, observation, tests, and documentation. Analysis of the data used in the analysis of qualitative and quantitative data. The results showed in the first cycle mathematical problem-solving ability has not been able to achieve success indicators with a percentage of completeness of 54.29%, then increased in the second cycle with a percentage of completeness of 77.14% to achieve an indicator of success. In cycle I student activities still need guidance with a value of 60.5 then increase in cycle II with a value of 84 is enough. The skills of the teacher got a good predicate in the first cycle with the achievement of achieving 81.43% and increased to very good in the second cycle with the achievement of 87.85% success.